Pengaruh Ekspor dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi Kreatif di Indonesia - Rizkina, Azka; Nova, Nova; Aidar, Nur; Rasyidin, M. (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The creative economy is a sector that has potential and is the latest source of economic growth as the government's solution to prevent the national economy from slowing down in recent years. There are several creative economy sectors that have an important role in increasing the growth of the creative economy in Indonesia. One indicator of the creative economy sector that has good performance is exports, where exports are a component of GDP. This means that if there is an increase in creative industry exports, then GDP originating from the creative economy will increase and ultimately increase national economic growth. Labor also plays an important role in increasing the growth of the creative economy. The aim of this research is to see the influence of exports and labor on the growth of the creative economy in Indonesia. This study uses a quantitative approach. The data used is secondary data from 2010-2022. The research results show that the export variable has no effect on the growth of the creative economy, while the labor variable has a positive effect on GDP. If the labor variable increases by 1%, the growth of the creative economy in Indonesia will also increase by 0.07%.